2021
DOI: 10.1111/bph.15606
|View full text |Cite
|
Sign up to set email alerts
|

Honokiol inhibits proliferation of colorectal cancer cells by targeting anoctamin 1/TMEM16A Ca2+‐activated Cl channels

Abstract: Background and Purpose Ca2+‐activated Cl− channels (Ano1 channels) contribute to the pathogenesis of colorectal cancer. Honokiol is known to inhibit cell proliferation and tumour growth in colorectal cancer. However, the molecular target of honokiol remains unclear. This study aimed to investigate whether honokiol inhibited cell proliferation of colorectal cancer by targeting Ano1 channels. Experimental Approach Patch‐clamp techniques were performed to study the effect of honokiol on Ca2+‐activated Cl− current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…HON is a natural product isolated from the bark of Houpu magnolia (Magnolia officinalis) and has been used as a traditional Chinese medicine. Recent studies reported that HON inhibited cancer cell proliferation and in vivo tumor growth, regulated the progression of inflammation, and inhibited bacterial growth over a wide range of temperatures and pH, and thereby reduced biofilm formation and antibiotic resistance (Chen et al, 2021;Chiu et al, 2021;Wang et al, 2021). Our results showed that HON treatment decreased the level of HMGB1 and inflammatory factors, and protected against intestinal barrier dysfunction.…”
Section: Discussionsupporting
confidence: 62%
“…HON is a natural product isolated from the bark of Houpu magnolia (Magnolia officinalis) and has been used as a traditional Chinese medicine. Recent studies reported that HON inhibited cancer cell proliferation and in vivo tumor growth, regulated the progression of inflammation, and inhibited bacterial growth over a wide range of temperatures and pH, and thereby reduced biofilm formation and antibiotic resistance (Chen et al, 2021;Chiu et al, 2021;Wang et al, 2021). Our results showed that HON treatment decreased the level of HMGB1 and inflammatory factors, and protected against intestinal barrier dysfunction.…”
Section: Discussionsupporting
confidence: 62%
“…High-throughput drug screening and computer-aided drug design have identified an array of TMEM16A activators and potentiators, among which ETX001, a potentiator of TMEM16A, has entered clinical trials as therapeutic agent for cystic fibrosis ( 7 ). Meanwhile, a large number of TMEM16A inhibitors have been identified, including natural products Cepharanthine ( 8 ), Evodiamine ( 9 ), Honokiol ( 10 ), and Luteolin ( 11 ) and synthetic compounds Ani9 ( 12 ), CaCC inh -A01 ( 13 ), T16A inh -A01 ( 14 ), Monna ( 15 ), and 4-arylthiophene-3-carboxylic acid ( 16 ). These inhibitors have shown potential therapeutic effects in the laboratory against TMEM16A-related diseases such as hypertension, cancer, and secretory diarrhea ( 7 ).…”
mentioning
confidence: 99%
“…The role of honokiol includes the induction of apoptosis and autophagy in osteosarcoma cells by ROS/ERK1/2 signaling [ 30 ], suppression of pancreatic cancer progression, and invasion by miR-101/Mcl-1 and SMAD2/3 axis [ 27 , 43 ], reduction of gastric tumor growth and peritoneal dissemination by inhibiting Tpl2 [ 44 ], and antagonism of doxorubicin resistance in breast cancer through miR-188-5p/FBXW7/c-Myc pathway [ 45 ]. It has also been reported that honokiol can inhibit colon cancer cell proliferation through signals such as TGF-β1/p53 [ 21 , 46 ], but only one paper revealed that the death mode induced by honokiol might be iron death [ 47 ]. Honokiol can also increase the sensitivity of tumor cells to cisplatin and oxaliplatin [ 47 , 48 ].…”
Section: Discussionmentioning
confidence: 99%